Pemberdayaan Remaja “MALAQBI “sebagai Peer Group Kesehatan Reproduksi di Kelurahan Baurung, Kecamatan Banggae, Kabupaten Majene, Sulawesi Barat. - Wahida Munir; Aswar Aswar; Pattola Pattola; Nurpadila Nurpadila; Immawanti Immawanti (Yayasan Inspirasi El Burhani, 2026)
Introduction: Reproductive health is an essential component of adolescent development, particularly for adolescent girls who experience significant physical, psychological, and social changes. Limited knowledge and inadequate access to accurate reproductive health information increase the risk of reproductive health problems. Therefore, community-based reproductive health education is needed to empower adolescent girls to adopt healthy reproductive behaviors. Objective: This community service program aimed to improve the knowledge, attitudes, and behaviors of adolescent girls regarding reproductive health through a community-based health education program. Methods: This community service employed a one-group pretest-posttest design involving 30 adolescent girls aged 14–19 years in Baurung Village, Majene Regency. The intervention consisted of interactive health education sessions, group discussions, educational games, demonstrations using reproductive organ models, and the distribution of educational booklets and posters. Participants' knowledge, attitudes, and behaviors were assessed before and after the intervention using a structured questionnaire. Results: The program demonstrated positive outcomes across all evaluated domains. The mean knowledge score increased from 52% before the intervention to 87% after the intervention. Attitude scores improved from 45% to 84%, while behavior scores increased from 44% to 83%. Participants also showed greater awareness of reproductive hygiene, adolescent developmental changes, and appropriate reproductive health practices. Conclusion: Community-based reproductive health education effectively improved the knowledge, attitudes, and behaviors of adolescent girls regarding reproductive health. The findings suggest that a peer-group empowerment approach can be adopted as a sustainable community-based strategy to strengthen adolescent reproductive health promotion and prevention programs.